Pembinaan dan penilaian modul sintaksis asas Bahasa Arab berlandaskan pendekatan kontrastif Bahasa Melayu – Bahasa Arab / Siti Aishah Ashaari - Siti Aishah , Ashaari (2016)
This study aims to identify the similarities and differences of the basic syntax of Arabic and Malay language by using the contrastive approach, to identify the level of difficulty of students to the elements of Arabic grammar contained in DSKP Arabic Year 4 KSSR and to develop the Basic Syntax Arabic Module (M-SABA) and assess the effectiveness of the module. The Instructional Design of Dick and Carey Model (2005) were used as the basis for the construction Basic Syntax Arabic Module (M-SABA) Contrastive based approach. The study was divided into three sections, namely, the qualitative study based approach contrastive, descriptive study design and a quasi-experimental study design. The sample consisted of 154 students from 4 years from four primary schools in the state of Pulau Pinang. A total of 79 students from the treatment group and 75 students from the control group. Instrument Arabic grammar proficiency tests were used to determine the level of difficulty of researchers towards the elements of Arabic grammar contained in Arabic DSKP Year 4 KSSR. While the instruments of the pre-test and post-test was used to assess the effectiveness of the modules developed by the researchers to compare the achievement of students in the construction of basic paragraph basic language syntax Arab. The finding of comparison shows patterns of basic sentence patterns Malay are similar with nominal sentences in Arabic. But there are differences of gender and number of compatibility between subject and predicate. The findings also indicate grammatical elements most difficult to master by student is the compatibility of plural elements followed by, the compatibility of the feminine gender and compatibility masculine gender. The results also indicated that most elements are controlled by them is classification of prepositions and the classification of the noun. The results of the study hypothesis suggests teaching using a quasiexperimental module Basic Syntax Arabic (M-SABA) developed by contrastive approach is more effective than conventional approaches in improving basic skills in producing paragraph based Arabic language basic syntax. The finding also has a major impact on the pedagogy of teaching Arabic in schools in Malaysia, thus a model of teaching Arabic language basic syntax M-SABA has been proposed. This module is expected to be utilised efectively and provide chances for future reseachers to improve the module for more efective teaching and learning process.